SLC19A1 80G allele as a biomarker of methotrexate-related gastrointestinal toxicity in Portuguese rheumatoid arthritis patients. (April 2014) - Lima, Aurea; Bernardes, Miguel; Sousa, Hugo; Azevedo, Rita; Costa, Lúcia; Ventura, Francisco; Seabra, Vítor; Medeiros, Rui
Aim: The aim of our study was to characterize the association of clinicopathological variables and the SLC19A1/RFC-1 G80A polymorphism in methotrexate (MTX)-related toxicity in Portuguese patients with rheumatoid arthritis.Patients & methods: The study included 233 consecutively recruited patients with rheumatoid arthritis under MTX treatment. The SLC19A1 G80A polymorphism was evaluated by PCR-RFLP.Results: Statistical analysis revealed that SLC19A1 80G carriers had increased risk of gastrointestinal toxicity (odds ratio [OR]: 2.61, p = 0.019) and that regular folic acid supplementation was associated with both overall and gastrointestinal toxicity protection (OR: 0.15, p < 0.001 and OR: 0.19, p < 0.001, respectively). Multivariate analysis confirmed the association of SLC19A1 80G and regular folic acid supplementation to gastrointestinal toxicity (OR: 5.53 and 0.13, respectively). Moreover, a multivariate Cox regression model demonstrated a higher risk of earlier gastrointestinal toxicity in SLC19A1 80G carriers (hazard ratio: 3.63, p = 0.002).Conclusion: SLC19A1 G80A genotyping may be a useful tool for clinicians to identify patients at higher risk for developing gastrointestinal toxicity related to MTX treatment. Original submitted 16 October 2013; Revised submitted 4 December 2013